Big George how a shy boy became President Washington - Phelan, Matt 1970- (Harcourt, 2009)
Portrays George Washington as a shy boy who wasn't afraid of anything except talking to people, but who grew up to lead an army against the British and serve as president of the new nation
Illustrations done in pencil and gouache
Includes bibliographical references (T.p. verso)
Keywords: Washington, George / 1732-1799 / Juvenile literature; Washington, George / 1732-1799; Presidents / United States / Biography / Juvenile literature; Presidents; USA; Biografie